2014
DOI: 10.1051/0004-6361/201424419
|View full text |Cite
|
Sign up to set email alerts
|

The GALEX Ultraviolet Virgo Cluster Survey (GUViCS)

Abstract: We study the role of the environment on galaxy evolution using a sample of 868 galaxies in the Virgo cluster and in its surrounding regions that are selected from the GALEX Ultraviolet Virgo Cluster Survey (GUViCS) with the purpose of understanding the origin of the red sequence in dense environments. The sample spans a wide range in morphological types (from dwarf ellipticals to Im and BCD) and stellar masses (10 7 M star 10 11.5 M ). We collected multifrequency data covering the whole electromagnetic spectru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
266
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(292 citation statements)
references
References 139 publications
(192 reference statements)
26
266
0
Order By: Relevance
“…This picture is supported by observations of local clusters, which find very few star-forming satellites at stellar masses of 10 9.5 M versus the ∼ 30% quenched fraction measured for group and Milky Way-like hosts (e.g. Smith et al 2012;Boselli et al 2014b;Phillips et al 2015;Sánchez-Janssen et al 2016). …”
Section: Reproducing the Critical Mass Scale For Satellite Quenchingsupporting
confidence: 53%
“…This picture is supported by observations of local clusters, which find very few star-forming satellites at stellar masses of 10 9.5 M versus the ∼ 30% quenched fraction measured for group and Milky Way-like hosts (e.g. Smith et al 2012;Boselli et al 2014b;Phillips et al 2015;Sánchez-Janssen et al 2016). …”
Section: Reproducing the Critical Mass Scale For Satellite Quenchingsupporting
confidence: 53%
“…In this region the sky coverage is 94% (Boselli et al 2014a) at the depth of the All Imaging Survey (AIS), where the completeness is 20 mag, and 65% at the depth of the Medium Imaging Survey (MIS; 21.5 mag) 1 . Unfortunately, because of a failure of the farultraviolet (FUV) detector, this survey was completed only in the NUV.…”
Section: The Datamentioning
confidence: 99%
“…Boselli et al , 2008aBoselli et al ,b, 2014a). The UV data extracted from this survey have been recently published in Voyer et al (2014), and the study of the physical properties of Virgo cluster galaxies derived from a multifrequency analysis have been presented in Boselli et al (2014a). In two other companion papers we presented the study of the extraplanar star formation activity of a few gas stripped galaxies in the cluster (Boissier et al 2012) and of the diffuse Galactic emission of the UV scattered light in the Virgo direction (Boissier et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Subclusters around the ellipticals M86 and M49 (whose systemic velocities are, respectively, −181 and 950 km s −1 , Kim et al 2014) are merging with the main cluster around the central elliptical M87. Several H I imaging surveys of the cluster revealed that the H I discs of its central late-type galaxies are truncated to well within the optical discs, suggesting that ICM-ISM interactions play an important role in driving the evolution of galaxies in the inner region of the cluster (Warmels 1988;Cayatte et al 1990;Chung et al 2009;Boselli et al 2014). Wide-area H I surveys like HIPASS (H I Parkes All-Sky Survey, Barnes et al 2001), ALFALFA (Arecibo Legacy Fast ALFA, Giovanelli et al 2005) and AGES (Arecibo Galaxy Environment Survey, Auld et al 2006) done with singledish telescopes have helped detect many low H I mass galaxies such as early-type and late-type dwarf galaxies, but also starless dark galaxies and several H I clouds (e.g.…”
Section: Introductionmentioning
confidence: 99%